2009
DOI: 10.1243/13506501jet420
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thermally sprayed micro- and nanocrystalline cylinder wall coatings by means of a cavitation test

Abstract: The future development of motor engine design and technology governs the increasingly demanding requirements on materials in terms of friction and wear properties. In order to reduce emissions and achieve economical and environmentally sound solutions, thermal-spray processes became an interesting alternative to manufacture wear resistant and low-friction cylinder surfaces. Three thermal-spray processes are of major interest: twin wire arc system, high-velocity oxygen fuel and plasma transferred wire arc. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A series of Fe-based amorphous coatings were prepared by arc spraying process recently. The investigation showed they had higher hardness, better corrosion, wear and cavitation erosion resistance compared to the conventional crystalline materials [9][10][11][12][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A series of Fe-based amorphous coatings were prepared by arc spraying process recently. The investigation showed they had higher hardness, better corrosion, wear and cavitation erosion resistance compared to the conventional crystalline materials [9][10][11][12][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have reported that cracks and pores are primary spots for initiating the cavitation wear. 35 Because the purpose of the current work is to develop the clads, which shows more resistance against cavitation wear, the clads must be defect-free and less porous. Figure 9 shows the optical micrograph images of porosity in different clad regions of the developed clad.…”
Section: Porosity Measurementmentioning
confidence: 99%
“…However, this material increases the manufacturing process and cost. Besides, surface strengthening techniques were also employed to strengthen the inner wall of the aluminum alloy cylinder, such as inner hole thermal spraying [14][15][16][17][18][19], electroplating [20], and coating [21], having the advantages of simple operation, high efficiency and low cost.…”
Section: Introductionmentioning
confidence: 99%